Análise do uso normativo dos precedentes na motivação das decisões judiciais no direito brasileiro - Mattos, Lucas de Brandão e (2019)
In the Brazilian judicial practice and legislation itself, judicial precedents have grown quite powerful in recent years, lacking, however, a comprehensive and theoretical study on the legitimacy of the use of these precedents as normative basis of a judicial decision. The present study aims to conduct a critical study on the current situation of the use of judicial precedents in Brazilian law, both from the point of view of the mistakes made in its practical use, and the doctrine that supports this practice, seeking to realize an analysis of the precedents in the common law and its possibilities of transition to Brazilian law. It begins with the identification of better addressing the issue Rise of the Judiciary and the appreciation of jurisprudence as a framework which seeks to provide effective binding judicial precedents, finally analyzing the Brazilian doctrine of precedent that supports its effectiveness as an element of standardization and spatial coherence. The subsequent part aims at the analysis of the dynamics of precedent in common law and all correlate to the same context, it becomes possible to observe that the foundations of national doctrine do not match the experience previous developed that system. Finally, the analysis in the light of the constitutional duty of justification of judicial Decisions calls for greater control in the judicial activity and a decision model that can generate by itself a coherent system necessary for the proper functioning of the legal system